PENGEMBANGAN E-LKPD BERBANTUAN CLASSPOINT PADA MATERI TEKS NARASI DI KELAS IV SEKOLAH DASAR - Safitri, Adinda Serli; Ahmad Syarif; Febby Ayuni Esya Putri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to develop E-LKPD assisted by ClassPoint on narrative text material in grade IV of Elementary School and analyze its level of validity and practicality. The background of the study is based on the results of observations in grade IV of SDN 14/I Sungai Baung which showed that students still have difficulty in composing narrative texts coherently, understanding the structure (orientation, complication, resolution), and identifying intrinsic elements of the text. In addition, learning is still dominated by conventional methods and the use of printed LKPD without the support of interactive digital media, even though the school facilities are adequate. This study uses the Research and Development (R&D) method with the ADDIE model which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The trial subjects consisted of 6 students in the small group test, 25 students in the large group test, and 1 grade IV teacher. The research instruments were in the form of expert validation questionnaires (materials, media, and language) as well as teacher and student response questionnaires. Data were analyzed using quantitative descriptive techniques with the formula for the percentage of validity and practicality. The research results show that the ClassPoint-assisted e-LKPD meets the valid criteria based on expert assessment and is considered practical based on teacher and student responses. Therefore, the developed e-LKPD is suitable for use in Indonesian language learning for narrative texts in fourth grade elementary schools.